2023
DOI: 10.1111/1750-3841.16719
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in extending the shelf life of fresh wet noodles: Influencing factors and preservation technologies

Abstract: Fresh wet noodles (FWNs) are popular among people and have attracted increasing attention because of their characteristics of freshness, chewiness, good taste, and better maintenance of noodle flavor. However, due to the high moisture content and abundance of nutrients in FWN, they are prone to spoilage, which shortens their shelf life and reduces their quality, greatly restricting their large‐scale production. Therefore, seeking effective preservation methods to prolong the shelf life is a major breakthrough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 126 publications
0
0
0
Order By: Relevance
“…These results suggest that adding PSAL within a specific range can enhance noodle quality and improve palatability. This observation aligns with the findings of Obadi et al [37], who demonstrated that alterations in noodle hardness, chewiness, and adhesiveness contribute to enhancing noodle quality.…”
Section: Effect Of Psal On the Textural Properties Of Noodlessupporting
confidence: 92%
“…These results suggest that adding PSAL within a specific range can enhance noodle quality and improve palatability. This observation aligns with the findings of Obadi et al [37], who demonstrated that alterations in noodle hardness, chewiness, and adhesiveness contribute to enhancing noodle quality.…”
Section: Effect Of Psal On the Textural Properties Of Noodlessupporting
confidence: 92%
“…Cold plasma modifies protein structures through the production of reactive oxygen species (ROS), reactive nitrogen species (RNS), free radicals, and high-speed electrons. These reactive species induce changes in proteins, such as chemical bond formation, amino acid side chain oxidation, and polypeptide chain cross-linking, thereby improving protein functionality [24,25]. Therefore, investigating the changes in protein functional characteristics following cold plasma treatment is essential for unlocking the practical value of this technology.…”
Section: Introductionmentioning
confidence: 99%